Risk factors associated with self‐reported Q fever in Australian wildlife rehabilitators: Findings from an online survey. (12th October 2022) - Mathews, Karen O.; Savage, Cathie; Norris, Jacqueline M.; Phalen, David; Malikides, Nick; Sheehy, Paul A.; Bosward, Katrina L.
Abstract: Australian wildlife rehabilitators (AWR) are at increased risk of developing Q fever, a serious zoonotic disease caused by the intracellular bacterium Coxiella burnetii . Previous studies have suggested that Australian wildlife may be a potential C. burnetii infection source for humans. However, a recent serological survey of AWR found no association between C. burnetii exposure and direct contact with any wildlife species. To further explore the potential risk that wildlife may pose, this study aimed to identify associations between self‐reported Q fever in AWR and risk factors for exposure to C. burnetii . An online cross‐sectional survey was implemented in 2018 targeting AWR nationwide. Risk factors for self‐reported Q fever were determined using multivariable logistic regression. Medically diagnosed Q fever was self‐reported in 4.5% (13/287) of unvaccinated respondents. Rehabilitators who self‐reported medically diagnosed Q fever were significantly more likely to: primarily rehabilitate wildlife at a veterinary clinic (OR 17.87, 95% CI: 3.09–110.92), have domestic ruminants residing on the property where they rehabilitate wildlife (OR 11.75, 95% CI: 2.91–57.42), have been educated at a High School/Technical and Further Education level (OR 10.29, 95% CI: 2.13–84.03) and be aged >50 years (OR 6.61, 95% CI: 1.60–38.35). No association was found between self‐reported Q fever and direct contact with wildlife. These findings support previous work suggesting that AWR are at increased risk of C. burnetii infection and may develop Q fever potentially via exposure to traditional infection sources including livestock, other domestic animals, or contaminated environments, in association with their rehabilitation practices and lifestyle. Although Q fever vaccination is recommended for AWR, vaccine uptake is low in this population. Future studies should aim to determine the level of Q fever awareness and identify barriers to Q fever vaccination in this at‐risk group. The difficulty in accessing the AWR population also highlights the need for a national centralized AWR database.